Boosting NAD+ with a small molecule that activates NAMPT - Stephen J. Gardell (Nature Portfolio, 2019)
Nicotinamide phosphoribosyltransferase (NAMPT) catalyzes the rate determining step for NAD+ synthesis and is of interest as a drug target. Here the authors identify and characterize a small molecule NAMPT activator SBI-797812, elucidate its mode of action and show that it increases intracellular NMN and NAD+ levels in cultured cells and elevates liver NAD+ in mice.